Cytoplasmic FLIP(S) and nuclear FLIP(L) mediate resistance of castrate-resistant prostate cancer to apoptosis induced by IAP antagonists. Issue 11 (November 2018) - McCann, Christopher; Crawford, Nyree; Majkut, Joanna; Holohan, Caitriona; Armstrong, Chris; Maxwell, Pamela; Ong, Chee; LaBonte, Melissa; McDade, Simon; Waugh, David; Longley, Daniel
Abstract Expression of tumor necrosis factor-α (TNFα) in the serum of prostate cancer patients is associated with poorer outcome and progression to castrate-resistant (CRPC) disease. TNFα promotes the activity of NFκB, which regulates a number of anti-apoptotic and proinflammatory genes, including those encoding the inhibitor of apoptosis proteins (IAPs); however, in the presence of IAP antagonists, TNFα can induce cell death. In the presence of recombinant or macrophage-derived TNFα, we found that IAP antagonists triggered degradation of cIAP1 and induced formation of Complex-IIb, consisting of caspase-8, FADD and RIPK1 in CRPC models; however, no, or modest levels of apoptosis were induced. This resistance was found to be mediated by both the long (L) and short (S) splice forms of the caspase-8 inhibitor, FLIP, another NFκB-regulated protein frequently overexpressed in CRPC. By decreasing FLIP expression at the post-transcriptional level in PC3 and DU145 cells (but not VCaP), the Class-I histone deacetylase (HDAC) inhibitor Entinostat promoted IAP antagonist-induced cell death in these models in a manner dependent on RIPK1, FADD and Caspase-8. Of note, Entinostat primarily targeted the nuclear rather than cytoplasmic pool of FLIP(L). While the cytoplasmic pool of FLIP(L) was highly stable, the nuclear pool was more labile and regulated by the Class-I HDAC target Ku70, which we have previously shown regulates FLIP stability. The efficacy of IAP antagonist (TL32711) and Entinostat combination and their effects on cIAP1 and FLIP respectively were confirmed in vivo, highlighting the therapeutic potential for targeting IAPs and FLIP in proinflammatory CRPC.